MISTERIJA ŠAHOVSKE IGRE - Dragan Drobnjak (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2006)
If we relife of enigmatic, unexplainable, and partly mysterious, the chess game would lose much of its genuine nature, which wouldne, to be characterized any more by that original allure of enchanting.Chess game does not reveal all its secrets neither in regard to its origin nor in regard to its place in the life of an individual or the society.Therefore, chess game is extremely interesting filed of research from the sociological, socio-psychological, anthropological, cultural and other aspects. While elaborating this theme from all these aspects i have tried to come up with the answer to the question:Where is the beginning and the end of the chess game?On this questin, until now no one has given the precise answer, the answer which acknoweledges the thesis that mystery of the chess game has not yet been resolved, and we dont, know if will be and when it will be resolved.